An Unusual Case of Clear Cell Chondrosarcoma with Very Late Recurrence and Lung Metastases, 29 Years after Primary Surgery - Minna Laitinen; Jyrki Nieminen; Toni-Karri Pakarinen (Case Reports in Orthopedics)
Clear cell chondrosarcoma is a rare bone neoplasm with low-grade clinical course and the potential to metastasize to the skeleton and lungs. The aim of this report is to present a case that is extremely rare, but in accordance with the literature where the clear cell chondrosarcoma reportedly has a tendency for late metastases. In our patient the primary surgery was intralesional, since it was mistakenly interpreted as a benign tumour in the early 80s. The local recurrence and lung metastases occurred, however, 29 years after the initial treatment. The local recurrence was resected with wide margins, no additional surgery or oncological treatments were given, and two and half years postoperatively patient is doing well and there is no progression in the disease. In conclusion, it is important to have a long follow-up to the clear cell chondrosarcoma patients even for decades or lifelong, because the malignancy tends to metastasize or recur after an extended period. The course of metastasized disease may be unusually slow, so relatively aggressive treatment in metastasized and recurring cases is justified.